Reasons for accepting or declining Down syndrome screening in Dutch prospective mothers within the context of national policy and healthcare system characteristics: a qualitative study. Issue 1 (December 2016) - Crombag, Neeltje; Boeije, Hennie; Iedema-Kuiper, Rita; Schielen, Peter; Visser, Gerard; Bensing, Jozien
Abstract Background Uptake rates for Down syndrome screening in the Netherlands are low compared to other European countries. To investigate the low uptake, we explored women's reasons for participation and possible influences of national healthcare system characteristics. Dutch prenatal care is characterised by an approach aimed at a low degree of medicalisation, with pregnant women initially considered to be at low risk. Prenatal screening for Down syndrome is offered to all women, with a 'right not to know' for women who do not want to be informed on this screening. At the time this study was performed, the test was not reimbursed for women aged 35 and younger. Methods We conducted a qualitative study to explore reasons for participation and possible influences of healthcare system characteristics. Data were collected via ten semi-structured focus groups with women declining or accepting the offer of Down syndrome screening (n = 46). All focus groups were audio- and videotaped, transcribed verbatim, coded and content analysed. Results Women declining Down syndrome screening did not consider Down syndrome a condition severe enough to justify termination of pregnancy. Young women declining felt supported in their decision by perceived confirmation of their obstetric caregiver and reassured by system characteristics (costs and age restriction). Women accepting Down syndrome screening mainly wanted to be reassured or be prepared to care for a child with Down syndrome. By weighing up the pros and cons of testing, obstetric caregivers supported young women who accepted in the decision-making process. This was helpful, although some felt the need to defend their decision to accept the test offer due to their young age. For some young women accepting testing, costs were considered a disincentive to participate. Conclusions Presentation of prenatal screening affects how the offer is attended to, perceived and utilised. By offering screening with age restriction and additional costs, declining is considered the preferred choice, which might account for low Dutch uptake rates. Autonomous and informed decision-making in Down syndrome screening should be based on the personal interest in knowing the individual risk of having a child with Down syndrome and system characteristics should not influence participation.